Meningkatkan Kinerja Sumber Daya Manusia Melalui Knowledge Donating dan Perilaku Kerja Inovatif di Kecamatan Arut Selatan - Januar, Deni (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the ability of knowledge donating, innovative work behaviour in influencing human resource performance. We believe that the research results will be useful in encouraging managers to take steps and strategies to improve employee performance. The research was conducted at the South Arut District Government office, West Kotawaringin Regency with a sample of 71 participants. The method in this research uses statistical methods and data collection methods using primary and secondary data. The reliability test uses Cronbach Alpha and the validity test uses correlation and discriminant. Testing uses the Partial Least Square (PLS) method. The research results show that: Knowledge Donating has a positive relationship with Human Resource Performance, Innovative Work Behavior has a positive relationship with Human Resource Performance and Knowledge Donating has a positive relationship with Human Resource Performance through Innovative Work Behavior.